Antarctic Lichens under Long-Term Passive Warming: Species-Specific Photochemical Responses to Desiccation and Heat Shock Treatments - Marín, Catalina; Barták, Miloš; Palfner, Götz; Vergara-Barros, Pablo; Fernandoy, Francisco; Hájek, Josef; Casanova-Katny, Angélica (Plants (Basel, Switzerland), 2022)
Climate warming in the Antarctic tundra will affect locally dominant cryptogams. Being adapted to low temperatures and freezing, little is known about the response of the polar lichens' primary photochemistry to warming and desiccation. Since 2008, we have monitored the ecophysiological responses of lichens to the future warming scenario during a long-term warming experiment through open top chambers (OTCs) on Fildes Peninsula. We studied the primary photochemical response (potential Fv/Fm and effective efficiency of photosystem II YPSII) of different lichen taxa and morphotypes under desiccation kinetics and heat shock experiments. As lichens grow slowly, to observe changes during warming we methodologically focused on carbon and nitrogen content as well as on the stable isotope ratios. Endemic Himantormia lugubris showed the strongest effect of long-term warming on primary photochemistry, where PSII activity occurred at a lower %RWC inside the OTCs, in addition to higher Fv/Fm values at 30 °C in the heat shock kinetic treatment. In contrast, Usnea aurantiaco-atra did not show any effect of long-term warming but was active at a thallus RWC lower than 10%. Both Cladonia species were most affected by water stress, with Cladonia aff. gracilis showing no significant differences in primary photochemical responses between the warming and the control but a high sensibility to water deficiency, where, at 60% thallus RWC, the photochemical parameters began to decrease. We detected species-specific responses not only to long-term warming, but also to desiccation. On the other hand, the carbon content did not vary significantly among the species or because of the passive warming treatment. Similarly, the nitrogen content showed non-significant variation; however, the C/N ratio was affected, with the strongest C/N decrease in Cladonia borealis. Our results suggest that Antarctic lichens can tolerate warming and high temperature better than desiccation and that climate change may affect these species if it is associated with a decrease in water availability.
Keywords: thermal shock; nitrogen isotope; climate change; chlorophyll fluorescence